Characterization of the intraspecific variation within the nickel (Ni) hyperaccumulator species Senecio coronatus (Asteraceae): a preliminary analysis of genetic population structure and shoot proteome expression - Wolf, Michael (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references.